Assessment of macular thickness following cataract surgery in diabetic patients - Apurva H Suthar, (Asian Journal of Medical Sciences, 2023)
Background: Cataracts and diabetes very commonly coexist. While the results of cataract extraction (CE) procedure are astounding, patients with diabetes may have more unfortunate visual outcomes in comparison to their counterparts. Aims and Objectives: This study is planned to see the frequency of development of macular oedema (ME) in diabetic patients as compared to non-diabetics and also to see the progression of ME after cataract surgery. Materials and Methods: This prospective comparative study enrolled 100 diabetics and 100 non-diabetics undergoing cataract surgery fulfilling inclusion criteria. Complete ocular examination was done for both the groups preoperatively and postoperatively at 1 week, 1 month, and 3 months including central macular thickness evaluation using optical coherence tomography (OCT). Results: Improvement in visual acuity was observed in both the group but, non-diabetics achieved better visual acuity in comparison to diabetics. A significant increase in mean central foveal thickness (CFT) in diabetics and in non-diabetics post 1 month of surgery was observed; however, at 3 month, the difference was not significant. All the patients with mild, moderate, and severe non-proliferative diabetic retinopathy (NPDR) showed increment in the CFT from the baseline value but none of the patient of mild NPDR grade presented with new development of clinically significant macular edema on OCT. Conclusion: Cataract surgery causes a significant increase in macular thickness post 1 month of surgery in both diabetic and non-diabetics. Cataract surgery did not lead to the progression of stages of DR, although patients with all the three grades of DR showed increment in CFT from the baseline reference value.